2014
DOI: 10.3855/jidc.3584
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ompR gene in the acid adaptation and thermal resistance of Salmonella Enteritidis SE86

Abstract: Introduction: The objective of this study was to evaluate the involvement of the ompR gene in the acid adaptation and thermal resistance of S. Enteritidis SE86, responsible agent of more than 95 % of investigated food-borne diseases, throughout the last decade in Southern Brazil. In this study, we constructed a mutant strain of S. Enteritidis SE86 (ΔompR) that was attenuated by a knockout technique. The OmpR protein expression was determined in a tagged (3XFLAG) strain of S. Enteritidis SE86. Methodology: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Supporting this, the acid tolerance genes SEN1564A and cfa were upregulated in response to acid adaptation. SEN1564A encodes an acid shock protein in S. Enteritidis that is synthesized to repair or prevent acid-induced damage allowing bacterial survival at low pH (Álvarez-Ordóñez et al, 2011;Ritter et al, 2014). Cyclopropane fatty acid synthase encoded by cfa is also essential for the induction of ATR.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, the acid tolerance genes SEN1564A and cfa were upregulated in response to acid adaptation. SEN1564A encodes an acid shock protein in S. Enteritidis that is synthesized to repair or prevent acid-induced damage allowing bacterial survival at low pH (Álvarez-Ordóñez et al, 2011;Ritter et al, 2014). Cyclopropane fatty acid synthase encoded by cfa is also essential for the induction of ATR.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many scholars have discovered and identified protective proteins related to pH pressure. Most of the identified acid stress proteins involved in cell regulation, energy metabolism, molecular monitoring, transcription, translation, pili synthesis, cell signaling, and virulence (Ritter et al, 2014). It is reported that bacteria may activate different acid resistant systems under different pH conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To further study the limitations of the studied strains, as well as other bacteria, directed evolution processes could be applied to enhance the survival of the cells to vacuum or high/low temperatures. Moreover, some genes from extremophile species have been identified and related to thermal resistance (Gonzalez-Blasco et al, 2000;Zhang and Griffiths, 2003;Ritter et al, 2014), which could be introduced to the cells and characterized. However, thermal and vacuum resistance is not only a matter of genetics, but also of cell components and protein melting and degradation.…”
Section: Discussionmentioning
confidence: 99%